2018
DOI: 10.1016/j.jinorgbio.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

The trans -[Ru(PPh 3 ) 2 ( N , N -dimethyl- N ′-thiophenylthioureato-k 2 O,S)(bipy)]PF 6 complex has pro-apoptotic effects on triple negative breast cancer cells and presents low toxicity in vivo

Abstract: Triple negative breast cancer (TNBC) is a heterogeneous subtype of breast tumors that does not exhibit the expression of estrogen and progesterone receptors, neither the amplification of the human epidermal growth factor receptor 2 (HER-2) gene. Despite all the advances in cancer treatments, the development of new anticancer drugs for TNBC tumors is still a challenge. There is an increasing interest in new agents to be used in cancer treatment. Ruthenium is a metal that has unique characteristics and important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…The in vivo toxicity of (30) was assessed using a mice model. At the doses administered intraperitoneally (50 and 300 mg/kg), this compound did not lead to a change in the weight of the animal compared to the control groups, which is indicative of a low toxicity [129].…”
Section: Other Ruthenium Complexes For the Treatment Of Tnbcmentioning
confidence: 85%
See 1 more Smart Citation
“…The in vivo toxicity of (30) was assessed using a mice model. At the doses administered intraperitoneally (50 and 300 mg/kg), this compound did not lead to a change in the weight of the animal compared to the control groups, which is indicative of a low toxicity [129].…”
Section: Other Ruthenium Complexes For the Treatment Of Tnbcmentioning
confidence: 85%
“…Cominetti et al (2018) also reported a ruthenium(II) complex of acylthiourea, (30) ( Figure 10), which was also found to be active against TNBC tumor cells [129]. The inhibition of proliferation, migration, invasion, and adhesion was observed for cancer cells exposed to (30).…”
Section: Other Ruthenium Complexes For the Treatment Of Tnbcmentioning
confidence: 90%
“…NPMBC inhibit the growth of TNBC cells better than non-TNBC cells [66]. Furthermore, NPMBC of which effects are dose- [49,53,55,67] and time- [63,67] dependent could be more cytotoxic than platinum-based drugs [52,53,57,58,68]. For example, Biancalana et al [57] observed that ruthenium complexes have good cytotoxic activity, with IC 50 values substantially lower than the values obtained with cisplatin on MDA-MB-231 cells.…”
Section: Suppression Of Cancer Cell Viability In Association With Thementioning
confidence: 99%
“…However, available evidence suggests that their action could be mediated by the inhibition of matrix metalloproteinases (MMPs) [59], enzymes with the ability to degrade extracellular matrix proteins, after interaction with the αvβ3 integrin receptor [62]. Likewise, it has been suggested that NPMBC could inhibit epithelial-mesenchymal transition [65] and modify the structure of the actin cytoskeleton, interfering with the function of integrins [58,59] and under-regulating the phosphorylation of the focal adhesion kinase (FAK) [51]. No less important are the studies which highlight their role in inflammation [89,90].…”
Section: Migration Invasion And/or Metastasismentioning
confidence: 99%
See 1 more Smart Citation